Inheritance of Polycomb-dependent chromosomal interactions in Drosophila - Bantignies, Frédéric; Grimaud, Charlotte; Lavrov, Sergey; Gabut, Mathieu; Cavalli, Giacomo (Genes & development, 2003)
Maintenance of cell identity is a complex task that involves multiple layers of regulation, acting at all levels of chromatin packaging, from nucleosomes to folding of chromosomal domains in the cell nucleus. Polycomb-group (PcG) and trithorax-group (trxG) proteins maintain memory of chromatin states through binding at cis -regulatory elements named PcG response elements or cellular memory modules. Fab-7 is a well-defined cellular memory module involved in regulation of the homeotic gene Abdominal-B ( Abd-B ). In addition to its action in cis , we show here by three-dimensional FISH that the Fab-7 element leads to association of transgenes with each other or with the endogenous Fab-7 , even when inserted in different chromosomes. These long-distance interactions enhance PcG-mediated silencing. They depend on PcG proteins, on DNA sequence homology, and on developmental progression. Once long-distance pairing is abolished by removal of the endogenous Fab-7 , the derepressed chromatin state induced at the transgene locus can be transmitted through meiosis into a large fraction of the progeny, even after reintroduction of the endogenous Fab-7 . Strikingly, meiotic inheritance of the derepressed state involves loss of pairing between endogenous and transgenic Fab-7 . This suggests that transmission of nuclear architecture through cell division might contribute to inheritance of chromatin states in eukaryotes.